Self‐Assembled Surfactant‐Polyoxovanadate Soft Materials as Tuneable Vanadium Oxide Cathode Precursors for Lithium‐Ion Batteries. (9th February 2023) - McNulty, Rory C.; Penston, Keir; Amin, Sharad S.; Stal, Sandro; Lee, Jie Yie; Samperi, Mario; Pérez‐García, Lluïsa; Cameron, Jamie M.; Johnson, Lee R.; Amabilino, David B.; Newton, Graham N.
Abstract: The mixing of [V10 O28 ] 6− decavanadate anions with a dicationic gemini surfactant ( gem ) leads to the spontaneous self‐assembly of surfactant‐templated nanostructured arrays of decavanadate clusters. Calcination of the material under air yields highly crystalline, sponge‐like V2 O5 ( gem ‐V2 O5 ). In contrast, calcination of the amorphous tetrabutylammonium decavanadate allows isolation of a more agglomerated V2 O5 consisting of very small crystallites ( TBA ‐V2 O5 ). Electrochemical analysis of the materials' performance as lithium‐ion intercalation electrodes highlights the role of morphology in cathode performance. The large crystallites and long‐range microstructure of the gem ‐V2 O5 cathode deliver higher initial capacity and superior capacity retention than TBA ‐V2 O5 . The smaller crystallite size and higher surface area of TBA ‐V2 O5 allow faster lithium insertion and superior rate performance to gem ‐V2 O5 . Abstract : Decavanadate anions self‐assemble with a dicationic surfactant to form ordered arrays which, when calcined, yield highly crystalline V2 O5 . In contrast, calcination of alkylammonium decavanadate leads to smaller V2 O5 crystallites. The systems show contrasting, topology‐dependent performance as cathode materials in Li‐ion batteries, offering a route to the controlled preparation of V2 O5 electrode materials that balance energy and rate performance.